Epigenetic Silencing of Immune-Checkpoint Receptors in Bone Marrow- Infiltrating T Cells in Acute Myeloid Leukemia - Radpour, Ramin; Stucki, Miriam; Riether, Carsten; Ochsenbein, Adrian F. (Frontiers in Oncology, 2021)
Background: Immune-checkpoint (IC) inhibitors have revolutionized the treatment of multiple solid tumors and defined lymphomas, but they are largely ineffective in acute myeloid leukemia (AML). The reason why especially PD1/PD-L1 blocking agents are not efficacious is not well-understood but it may be due to contribution of different IC ligand/receptor interactions that determine the function of T cells in AML. Methods: To analyze the interactions of IC ligands and receptors in AML, we performed a comprehensive transcriptomic analysis of FACS-purified leukemia stem/progenitor cells and paired bone marrow (BM)-infiltrating CD4+ and CD8+ T cells from 30 patients with AML. The gene expression profiles of activating and inhibiting IC ligands and receptors were correlated with the clinical data. Epigenetic mechanisms were studied by inhibiting the histone deacetylase with valproic acid or by gene silencing of PAC1. Results: We observed that IC ligands and receptors were mainly upregulated in leukemia stem cells. The gene expression of activating IC ligands and receptors correlated with improved prognosis and vice versa. In contrast, a majority of IC receptor genes was downregulated in BM-infiltrating CD8+ T cell and partially in CD4+ T cells, due to pathological chromatin remodeling via histone deacetylation. Therefore, treatment with histone deacetylase inhibitor (HDACi) or silencing of PAC1, as a T cell-specific epigenetic modulator, significantly increased the expression of IC receptors and defined effector molecules in CD8+ T cells. Conclusions: Our results suggest that CD8+ T cells in AML are dysfunctional mainly due to pathological epigenetic silencing of activating IC receptors rather than due to signaling by immune inhibitory IC receptors which may explain the limited efficacy of antibodies that block immune-inhibitory ICs in AML.